Entanglements of Empire : Missionaries, Maori, and the Question of the Body - Ballantyne, Tony, 1972- (Book collections on Project MUSE., 2014)
The first Protestant mission was established in New Zealand in 1814, initiating complex political, cultural, and economic entanglements with Maori. Tony Ballantyne shows how interest in missionary Christianity among influential Maori chiefs had far-reaching consequences for both groups. Deftly reconstructing cross-cultural translations and struggles over such concepts and practices as civilization, work, time and space, and gender, he identifies the physical body as the most contentious site of cultural engagement, with Maori and missionaries struggling over hygiene, tattooing, clothing, and sexual morality. Entanglements of Empire is particularly concerned with how, as a result of their encounters in the classroom, chapel, kitche, and farmyard, Maori and English mutually influenced each other's worldviews. Concluding in 1840 with New Zealand's formal colonization, this book offers and important contribution to debates over religion and empire.